Upaya Diversifikasi Konstruksi Beton untuk Jenis Perkerasan Kaku di Atas Tanah Gambut - Etty Rabihati (Vokasi, 2017)
Abstract: Gamtos is an alternative construction by utilizing local soil that Peat becomes partof the structure of the pavement by adding Matos as its stabilization material. Matos® wasadded to peat soil at a ratio of 1 kg / m3 based on the optimum moisture content on the soiland then added cement 5- 25% by weight of soil. Then tested the mechanical properties of theUnconfined Compressive Strength (UCS) soil, which results will aplied in the implementationof an environmental road to further calculated material costs and implementation of its work,and then analyzed the comparison cost of work Gamtos with concrete work. From the resultsof research was the addition of the percentage Matos® to the largest peat soil is at 12%, itproduces CBR value of 3.75%, while the percentage of Matos® 3% + cement 8% yields CBRvalue of 6.4%, 6% cement percentage + 8% cement yields CBR value 7.4% and the addedpercentage of Matos® 9% + cement 8% yields 8% CBR value. For the required cost budgetper m2 for each of the most economical mixtures is a mixture of Matos® 3% of 8% cementadditions of Rp13,800.00.